Biogeographic distributions of microbial communities associated with anaerobic methane oxidation in the surface sediments of deep-sea cold seeps in the South China Sea - Jiang, Qiuyun; Jing, Hongmei; Liu, Hao; Du, Mengran (Frontiers in Microbiology, 2022)
Cold seeps are oasis for the microbes in the deep-sea ecosystems, and various cold seeps are located along the northern slope of the South China Sea (SCS). However, by far most microbial ecological studies were limited to specific cold seep in the SCS, and lack of comparison between different regions. Here, sediments from Site F/Haima cold seeps and Xisha trough in the SCS were used to elucidate the biogeography of microbial communities, with particular interest in the typical functional groups involved in the anaerobic oxidation of methane (AOM) process. Distinct microbial clusters corresponding to the three sampling regions were formed, and significantly higher gene abundance of functional groups were present in the cold seeps than trough. This biogeographical distribution could be explained by the geochemical characteristics of sediments. Phylogenetic analysis demonstrated that mcrA and pmoA genotypes were closely affiliated with those from wetland and mangroves where DAMO process frequently occurred; and highly diversified dsrB genotypes were revealed as well. In addition, significantly higher relative abundance of NC10 group was found in the Xisha trough, where had more predicted functions of denitrification and dissimilatory nitrate reduction. This suggested that N-DAMO process was more important in the hydrate-bearing trough, although its potential ecological contribution to AOM deserves further investigation. Our study also further demonstrated the necessity of combining functional genes and 16S rRNA gene to obtain a comprehensive picture of the population shifts of natural microbial communities among different oceanic regions.